Assessing the anticoagulant effect of dabigatran in children: An in vitro study. Issue 4 (April 2015) - Dietrich, Kevin; Stang, Linda; van Ryn, Joanne; Mitchell, Lesley G.
Abstract Objectives Age-related changes in the hemostatic system result in variation in response to anticoagulants and coagulation assays over childhood. This study used in vitro methods to determine i) optimum coagulation assays for dabigatran in children and ii) anticoagulant effect of dabigatran across pediatric age groups. Materials and Methods Pooled plasma samples from healthy children aged 0 to < 1, 1 to < 5, 5 to < 10, 10 to < 17 years and adults were spiked with increasing concentrations of dabigatran and the effect was assessed in five coagulation assays. The samples were also assessed for overall hemostasis potential using a fibrin clot formation and lysis assay. Results In all five coagulation assays, there were no differences in responses to dabigatran over all pediatric age groups. The international normalized ratio was the least sensitive measure. Activated partial thromboplastin time showed moderate sensitivity and a nonlinear response curve. Thrombin time (TT), dilute TT (dTT) and ecarin clotting time were linearly correlated with dabigatran concentrations; however, the ecarin time and TT were overly sensitive. In the overall hemostasis potential assay, increasing dabigatran concentrations delayed the initiation of clot formation and reduced the time to 50% clot lysis. The responses to initiation of clot formation and clot lysis were consistent across all pediatric groups and comparable to responses in adults. Conclusion The dTT is the most suitable assay for measuring dabigatran concentrations in children. Fibrin clot generation and lysis assay responses to dabigatran in children over all ages were consistent and comparable to those of adults.